Strategi Ekspor Produk UMKM ke Pasar Internasional - Dzilla Khoerunnisa; Layalia Auliaur Rahman; Mila Salbiyah; Pina Aulia Maharani; Syahla Mutia Aini (Teewan Journal Solutions, 2025)
Exporting is a crucial strategy for expanding market reach and enhancing the competitiveness of MSME products in the international arena. This study examines the export strategy implemented by Sahabat Putra Snack, a tempe chips producer from Bandung, in its effort to enter the Malaysian market. Using a qualitative descriptive method with a case study approach, the findings indicate that export success is driven not only by product quality but also by effective promotional strategies, intercultural communication, and the utilization of social media as an international marketing tool. Through the X platform (Twitter), the business successfully reached Malaysian consumers, promoted its products, and built trust through direct communication in English. Furthermore, efficient logistics, including affordable shipping services and secure packaging, supported the delivery process. This study provides a practical illustration that with digital and collaborative approaches, Indonesian MSMEs can independently and sustainably compete in global markets.